Upper Triassic miliolids of "Cucurbita group": aspects of the systematic classification - Senowbari-Daryan, Baba (Abhandlungen der Geologischen Bundesanstalt Wien, 2016)
Miliolid Foraminifera are an abundant group in Upper Triassic reefs and shallow-water carbonates. During the last decades numerous known and new foraminiferal genera, like Cucurbita, Amphorella, Spiriamphorella, Urnulinella, Pseudocucurbita, Paratintinnina, Costifera, Siculocosta, Hydrania, and Tignumparina were described from several Carnian and Norian-Rhaetian localities. Since the establishing of these genera several authors have tried to revise their systematic positions. The present paper addresses some of the issues of the previous determinations and classifications, adding new data and specimens. Genera Costifera, Siculocosta, and Urnulinella recently considered synonymous with Cucurbita, are re-introduced, as well as several species. Two species of the genus Cucurbita (C. minima and C. aggtelekensis) are described as new.
UnivIS-Import:2017-11-07:Pub.2016.nat.dgeo.IGM.LP.uppert
Keywords: Miliolid Foraminifera; Upper Triassic; shallow-water carbonates; Cucurbita group; classification